A Case for Christianizing the Christian Church. (July 2016) - Tahaafe‐Williams, Katalina
Abstract: In this article I argue that the work of evangelism must take place both within the church and outside the church. The evidence of decline in the church – particularly in the West–is not matched by the vibrancy of the church in the global South. In both regions however there is a demonstrable lack of depth in the quality of Christian discipleship. It was this issue which I sought to address in my work in the Uniting Church in Australia by addressing the need for catechetical programmes targeting young people in the "migrant" churches of our denomination. Before long it became clear that there was a desire from the whole church – both adults and young people ‐ to explore their faith and practice more deeply. The task is to "evangelize the baptized" (Arias), which prioritizes evangelization and catechesis. Evangelism is how the church with its good news of God's reign attracts people out there in the society by word and example. Evangelization takes place within the church and is the initial stage by which persons are led step by step to a first commitment to the Christian life of faith.